Formulation of aquafeed from soya solid waste (soya hampas - Agus Fery Budi Hartono, Mamat Nurhan (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Soya solid waste is one of the by-products from the processed soybeans in food manufacturing industries. The increase in production rate of freshwater aquaculture sector leads to high demand for aquafeed with complete diets. However, the cost for raw ingredients in commercially manufactured aquafeed especially fishmeal is expensive. Therefore, soya solid wastes were utilized as an alternative feed ingredient for source of plant proteins which can reduce the usage of fishmeal in aquafeed productions. In this study, different types of fungi such as Trichoderma reesei, TrichodemlO harzianllm and Aspergillus niger were used to ferment the soya solid wastes by the process of solid state fermentation to improve its nutritional values. Soya solid wastes treated with T. reesei showed better improvement in the nutritional contents with increased in crude protein and crude lipid level for 5.75% and 1.3% respectively and decreased in crude fiber level for 0.36% compared to the other fungi. Thus, 10%, 20%, 30% and control feeds which contained 10%, 20%, 30% of soya solid waste treated with T. reessei and absent of soya solid waste respectively were formulated and also tested on tilapias for two weeks. The results showed that there were no significant differences (P > 0.05) between the growth performances of the tilapias with all types of diet feeds. This project was successful since the protein level of all diet feeds were maintained at 30% level and the growth performance of all the tilapias were almost the same.